PENGGUNAAN MEDIA AUGMENT REALITY BERBASIS CANVA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPA SDN 3 GETAS - Atik Kurnia Jayanti; Novitasari, Novitasari; Daimul Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to develop a learning media in the form of Android-based Digital Augmented Reality Learning Media on the Solar System material for Class VI Elementary School Students. The development of Augmented Reality digital media follows the steps in the ADDIE model, namely: analysis, design, development, implementation and evaluation. However, this research was only carried out until the development stage. The subject of this research is Augmented Reality digital media which was assessed by 2 material experts, 2 teachers and 28 students. The object of this research is the validity of Augmented Reality digital media. Data collection was carried out using a questionnaire method using a five-point scale, and data analysis used a percentage formula. The percentage results from the material expert test, media expert test, teacher practicality, and student practicality are respectively: 93.99%, 85.99%, 91.25%, 92.5%, with very good qualifications. Thus, it can be concluded that Augmented Reality digital media is suitable and valid for use in the learning process.